Sports Event Satisfaction and Word-of-Mouth Intention - Revindo, Mohamad Dian; Widyasanti, Amalia Adininggar; Nusantoro, Nalindro; Siregar, Chairina Hanum (E-Journal of Tourism; Volume 10 Number 2 (September 2023)DO - 10.24922/eot.v10i2.102208, 2023)
A mega sports event is expected to bring immediate and long-term impact on the host country’s economy. In this study, we explore one of the possible long-term outcomes of the Jakarta-Palembang 2018 Asian Games in the tourism sector by estimating the factors influencing the intention of its international spectators and participants in spreading positive word-of-mouth (WOM) about Indonesia to their respective relatives, friends, and colleagues after the event. Based on the face-to-face survey conducted during the event, there were 1,914 usable responses from international athletes, country officials, committees-sport federations, journalists, and spectators. The results show that the respondents were more likely to spread positive WOM if they were male, had never traveled to Indonesia, had the experience of participating in other international sports events, were relatively older, had long periods of stay in Indonesia during the visit, and participated in the event as a non-athlete. Furthermore, satisfaction with the provisions of facilities, including venues, food and accommodations, telecommunications and internet access, easy match scheduling, safety and security, information services, and transportation arrangements, had positive effects on their intention to spread positive WOM, although only the last two factors were statistically significant. This paper also discusses the policy and academic implications of the findings.